Kulintja Nganampa Maa-kunpuntjaku (Strengthening Our Thinking): Place-Based Approaches to Mental Health and Wellbeing in Anangu Schools - Sam Osborne (The Australian Journal of Indigenous Education, 2013)
MindMatters, implemented by Principals Australia Institute, is a resource and professional development initiative supporting Australian secondary schools in promoting and protecting the mental health and social and emotional wellbeing of members of school communities, preferring a proactive paradigm (Covey, 1989) to the position of ‘disaster response’. While the MindMatters national focus has continued, grown and become embedded in schools since its beginning in 2000, MindMatters staff have also specifically sought to establish localised mental health and wellbeing (MHWB) promotion in Aboriginal and Torres Strait Islander communities that empowers local school and community groups to build on community values and intergenerational capacities for supporting the MHWB of young people. This article outlines the processes for successful practice that have been developed in a very remote Aboriginal school context, and highlights the strengths and benefits of this approach from the perspectives of Anangu (Pitjantjatjara/Yankunytjatjara people of Central Australia) educators. Using a community development approach, Anangu educators, skilled linguists, community members and MindMatters trained staff formed learning communities that recontextualised MHWB curriculum to be taught in Anangu schools. While critically reflecting on the process MindMatters has adopted, this article draws on the voices of A nangu to privilege the cultural philosophical positions in the discourse. In so doing, important principles for translating what is fundamentally a western knowledge system's construct into corresponding Anangu knowledge systems is highlighted. Through building on the knowledge base that exists in the community context, Anangu educators, school staff and community members develop confidence, shared language and capacity to become the expert educators, taking their knowledge and resources to other Anangu school communities to begin their MindMatters journey ‘Anangu way’. This process supports students as they engage in the school-based activities and build a language for reflecting on MHWB concerns, leading them to learn and practice ‘better ways of thinking and acting’ (Kulintja Palyantja Palya —the Pitjantjatjara language title for the MindMatters, ‘Anangu Way’ program).